2015
DOI: 10.1016/j.jnoncrysol.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Epoxide-assisted alumina aerogels by rapid supercritical extraction

Abstract: Aerogels offer a potential alternative to noble metals that could reduce both the cost and environmental impact associated with catalytic converter production. The environmental impact of the production of aerogel catalysts could be further reduced by using a rapid supercritical extraction (RSCE) technique, which reduces the time and solvent waste associated with aerogel preparation. Alumina aerogels, which have shown activity in catalyzing exhaust processing reactions, were prepared using an epoxide-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 32 publications
(71 reference statements)
1
17
1
Order By: Relevance
“…The formation and development of γ-alumina likely contributed to the improved catalytic performance for aerogels heat-treated to 750˚C prior to analysis. In previous work, we demonstrated that alumina aerogels exhibited modest catalytic activity [14]; however, the catalytic performance of the Co-Al aerogels described in the present work was significantly higher. We therefore conclude that the cobalt species in the aerogel are a significant source of catalytic activity.…”
Section: Resultscontrasting
confidence: 43%
See 4 more Smart Citations
“…The formation and development of γ-alumina likely contributed to the improved catalytic performance for aerogels heat-treated to 750˚C prior to analysis. In previous work, we demonstrated that alumina aerogels exhibited modest catalytic activity [14]; however, the catalytic performance of the Co-Al aerogels described in the present work was significantly higher. We therefore conclude that the cobalt species in the aerogel are a significant source of catalytic activity.…”
Section: Resultscontrasting
confidence: 43%
“…Cobalt-alumina (Co-Al) RSCE gels were fabricated using a modified version of an epoxide-based precursor recipe approach adapted from Baumann et al [21] for preparation of alumina RSCE aerogels [14]. First, 2.9 g of aluminum nitrate hexahydrate (Fluka Analytical, 99%) was dissolved in 20 mL of reagent-grade ethanol (denatured ethyl alcohol, Fisher Scientific).…”
Section: Sample Fabricationmentioning
confidence: 99%
See 3 more Smart Citations